2015
DOI: 10.3389/fnana.2015.00041
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging of the human cerebellar pathways and their interplay with cerebral macrostructure

Abstract: Cerebellar white matter (WM) connections to the central nervous system are classified functionally into the Spinocerebellar (SC), vestibulocerebellar (VC), and cerebrocerebellar subdivisions. The SC pathways project from spinal cord to cerebellum, whereas the VC pathways project from vestibular organs of the inner ear. Cerebrocerebellar connections are composed of feed forward and feedback connections between cerebrum and cerebellum including the cortico-ponto-cerebellar (CPC) pathways being of cortical origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 65 publications
3
80
0
Order By: Relevance
“…DTI analysis, including segmentation and regions of interest (ROI) determination, followed atlas-based methods and quality assurance protocols for serial stability (3234). These methods, critical in small-N samples, are ordered, anchored for motion and stability, and alternating to reduce cross terms and maximize signal-to-noise.…”
Section: Methodsmentioning
confidence: 99%
“…DTI analysis, including segmentation and regions of interest (ROI) determination, followed atlas-based methods and quality assurance protocols for serial stability (3234). These methods, critical in small-N samples, are ordered, anchored for motion and stability, and alternating to reduce cross terms and maximize signal-to-noise.…”
Section: Methodsmentioning
confidence: 99%
“…These descriptions from classical neuroanatomy are echoed in diffusion-weighted imaging of the cerebellar white matter (Salamon et al, 2007; Keser et al, 2015). For example, a diffusion-tensor imaging study of the human cerebellum revealed clear images of the inferior, middle, and superior cerebellar peduncles, as well as the fibers projecting to and from the cerebellum.…”
Section: Cerebellar Anatomy Structural and Functional Connectivity mentioning
confidence: 99%
“…The CPCT is one of the major cerebellar afferent pathways connecting the sensorimotor cortex and contralateral cerebellum via the middle cerebellar peduncle (MCP) (Grimaldi et al, ; Kamali, Kramer, Frye, Butler, & Hasan, ). Fibers from the premotor cortex, primary motor cortex, and associated sensory cortex project to the pontine nucleus and further project to the contralateral cerebellum via the MCP (Figure a) (Kamali et al, ; Keser et al, ). The CPCT transfers information for coordinating voluntary motor activity and timing to the dentate nucleus (Akakin et al, ).…”
Section: Introductionmentioning
confidence: 99%